EXPLORING THE CREATIVE ECONOMIC POTENTIAL THROUGH TRAINING ON THE PRODUCTION OF PINEAPPLE DODOL AS A MEANS OF SUPPORTING TOURISM VILLAGE IN PEGASING DISTRICT CENTRAL ACEH - Maimunah, Siti; Yusniar, Yusniar; Dian Putri, Yohana; Yurina, Yurina (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2022)
The purpose of this Community Partnership Program (PKM) is to utilize pineapple as a community agricultural product in the Pegasing area, especially in Kayu Kul Village to be processed into snacks, namely pineapple lunkhead which can be used as souvenirs for tourists who come to visit. Central Aceh. The training activities for making pineapple lunkhead are aimed at (1) introducing processed products made from pineapple. (dodol pineapple) (2) to provide additional knowledge and skills for pineapple farming communities. (3) as a creative economic effort that can increase the income of the pineapple farming community (4) it is hoped that the community can develop a home industry that produces pineapple dodol (5) it is hoped that the pineapple dodol produced by the pineapple farming community can become a characteristic of tourist souvenir snacks. The successful implementation of all community service activities is expected to have good benefits for the community in general and the growth of home industry players in particular.